Penerapan Terapi Murotal Al-Qur’an Terhadap Nyeri Pasien Post ORIF: Case Report - Fadhlurrahman; Syahruramdhani (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Background – Open Reduction Internal Fixation (ORIF) is a surgical procedure performed to install an internal fixation device that aims to unite several fractured bones. Fracture is a disturbance of the normal continuity of a bone. Surgical action on extremity fractures with ORIF can result in the emergence of pain in patients. Al-Qur'an murotal therapy can be a solution to reduce pain levels in post ORIF patients. Objective - This study aims to analyze the application of murotal therapy to reducing pain levels in post ORIF patients at PKU Muhammadiyah Yogyakarta Hospital. Methods - The method in this study uses a case report. The design in this study used descriptive based on the application of murotal therapy to reduce pain. Results – The results of this study prove that Al-Qur'an murotal therapy is effective for reducing pain in post ORIF patients. Suggestion – Post ORIF patients can apply effective Al-Qur'an murotal therapy to reduce pain in post ORIF patients.